HAPUSNYA HAK ATAS TANAH AKIBAT PEMANFAATANNYA TIDAK SESUAI PERUNTUKAN PEMBERIAN HAKNYA - Muhammad Rahfanni (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT In the context of the abolition of private land rights, the meaning of private land is the land of the above eigendom where the previous owner of this law applies as the citizens of both men and women haveThe same opportunity to acquire land rights and benefits for both the self and the family so that if a person obtains a right to land the person has attached to the land which is also accompanied by his / her obligationThe research that the authors describe is the legality of rights over which is inconsistent with the designation of gift wherever the unused land shall be deprived of rights to its land or abolished by all applicable legal provisions for whoever violates the resulting land into state landIn the process of the abolition of the right therein in this case the land agency needs a process or supervision that regulates penysesuain of land that is not in accordance with the granting of his rights and impose sanctions on the holder of land property rights as a deterrent effect so that if the land is used in accordance with the allocation will create effects mutual benefit owners of rights and society will be the achievement of the spirit of UUPA fair and always provide benefits